PELAKSANAAN TATA KELOLA PADA PT BPRS BOBATO LESTARI KOTA TIDORE KEPULAUAN - Ruray, Titiek Arafiani; Majojo, Muhammad Yasin (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The Islamic People's Financing Bank (BPRS) Bobato Lestari has recently grown, marked by the increasing number of customers and MSME empowerment programs as well as the variety of products offered by customers, this causes the implementation of Good Corporate Governance (GCG) at BPRS Bobato Lestari to become increasingly important.The purpose of this study was: to determine the implementation of Governance at the Bobato Lestari Sharia People's Financing Bank, Tidore Islands City. This study uses a qualitative research method with a case study/case study approach, and the information uses snowball sampling.The results of this study can be concluded that PT BPRS Bobato Lestari has implemented the five principles of Good Corporate Governance after the government issued a financial services authority regulation Number 24/POJK.03/2018 concerning Governance for Islamic People's Financing Banks.